Produksi Ubi Jalar (Ipomoea batatas L.) Pada Berbagai Dosis Pupuk Kalium Dan Waktu Pembalikan Batang - Cindy Maya Silvia; Nurleni Kurniawati; Syafiuddin Syafiuddin (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
Sweet potato (Ipomoea batatas L.) is a plant that has the potential to replace rice as a staple food. Efforts can be made to increase the yield of sweet potato production by fulfilling nutrients such as potassium fertilization, as well as turning the stems to prevent the production of tubers in each segment. The purpose of this study was to determine the effect of various doses of potassium fertilizer and time to turn the stems and their interactions on the growth and yield of sweet potato plants. This study used a randomized block design (RAK) with the first factor, namely the dose of potassium (KCl): 50 kg ha-1 (k1), 100 kg ha-1 (k2), and 150 kg ha-1 (k3). The second factor is the time of the stem reversal, namely: no reversal (po), 4 wap and 8 wap (p1), 8 mst and 12 wap (p2). The analysis of the observational data used ANOVA with the LSD further test with p <0.05. The results showed that various doses of potassium fertilizer had different effects on the growth of sweet potato plants. It is known that the KCl fertilizer dose of 50 kg ha-1 gives the best effect, namely giving the highest number of roots and the highest wet stubble weight. At the time of stem reversal, it was known that the reversal time of 4 WAP and 8 WAP had the best effect, namely increasing the highest dry weight, and there was no interaction between the dose of potassium fertilizer and the time of stem reversal on the growth and yield of sweet potato plants.